PARADIGMA LINGKUNGAN HIDUP PADA ERA REVOLUSI INDUSTRI 4.0 - Andi Yaqub (Al-'Adl, 2018)
Paradigm is a color that gives an impression of attitude and behavior. The bias of the paradigm towards self and beyond the human self can be tasted through deep understanding. Among the instruments that can be used is jurisprudence. To find out the depth of understanding and level of awareness, research was conducted on the academic community of IAIN Kendari in the frame of the 4.0 industrial revolution. In IAIN Kendari, the environmental fiqh paradigm that is understood to follow the paradigm style as stated in RI Law No. 32 of 2009 concerning Environmental Protection and Management including Sustainable Development; Ecological Sustainability; and conservation The supervision paradigm of the academic community in IAIN Kendari found that the achievement of work programs oriented to environmental preservation went well, self-understanding as a trustworthy human being. The campus learning climate has followed the standards of era transformation from manual/conventional services to online or electronic services. This illustrates the rate of participation of Kendari IAIN in the era of industrial revulsion 4.0 is very significant. The construction of the environmental fiqh paradigm in the era of industrial revolution in Kendari IAIN was based on problems with the concept of restoration towards a harmonious life, containing customs and obligations of the role and preservation of the environment as a basis for environmental awareness and responsibility. The integration of the dimensions of Islamic law (fiqh), adat/culture, and science then formulated the paradigm of nature lovers as a new paradigm for environmental preservation.